THE INFLUENCE OF A HERITAGE CITY BRANDING ON THE CITY"™S BRAND IDENTITY AND BRAND IMAGE, AND TOURISTS"™ VISITING DECISION - Fatmawati, Indah; Maharani, Anindya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
The growing emphasis on urban management has driven a trend toward city branding to enhance the city attractiveness. This study investigates the influence of city branding on the city"™s brand identity and brand image, and tourists"™ visiting decision. This study was done in a quantitative approach. The data was collected by distributing online questionnaire, targeting visitors of Yogyakarta city. A total of 216 respondents participated in this study, obtained using a purposive sampling method. The data was analyzed using Structural Equation Modeling (SEM) in AMOS 21.0. The results show that the city branding directly influences the brand identity and visiting decision, but does not directly influence the brand image. Furthermore, the brand identity has a positive, significant and direct influence on the brand image and visiting decision. The brand identity mediates the influence of city branding on the visiting decision. The brand identity also mediates the influence of city branding on the brand image. Lastly, the brand image mediates the influence of brand identity on the visiting decision.JEL: M30, M31, M39.